1998
DOI: 10.1177/136346159803500208
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation and Suicide Attempts among Mexican Americans, Puerto Ricans and Cuban Americans

Abstract: This article compares the prevalence and sociodemographic correlates of suicidal ideation and suicide attempts in three Hispanic populations in the US: Mexican Americans, Cuban Americans, and Puerto Ricans. Lifetime reports of suicidal thought and behavior of adults participating in the 1982-1984 Hispanic Health and Examination Survey (HHANES) were analyzed. Puerto Ricans reported consistently higher rates of suicidal ideation and attempts than either Mexican Americans or Cuban Americans. The correlates of sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 40 publications
3
35
0
Order By: Relevance
“…The most consistent finding is a higher rate of lifetime suicide attempts among Puerto Ricans, and a lower rate among Cuban Americans (Fortuna et al, 2007; Monk et al, 1974; Oquendo et al, 2004; Ungemack et al, 1998). However, one study did not find significant differences in rates of suicidal ideation or attempts across Hispanic subgroups after adjusting for demographic, psychiatric and sociocultural factors (Fortuna et al, 2007).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The most consistent finding is a higher rate of lifetime suicide attempts among Puerto Ricans, and a lower rate among Cuban Americans (Fortuna et al, 2007; Monk et al, 1974; Oquendo et al, 2004; Ungemack et al, 1998). However, one study did not find significant differences in rates of suicidal ideation or attempts across Hispanic subgroups after adjusting for demographic, psychiatric and sociocultural factors (Fortuna et al, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Of the few studies that have examined rates of suicide ideation and attempts among different Hispanic ethnic subgroups, the bulk have found significant differences across subgroups (Fortuna et al, 2007; Monk & Warshauer, 1974; Oquendo et al, 2004; Ungemack & Guarnaccia, 1998). The most consistent finding is a higher rate of lifetime suicide attempts among Puerto Ricans, and a lower rate among Cuban Americans (Fortuna et al, 2007; Monk et al, 1974; Oquendo et al, 2004; Ungemack et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Many have highlighted the need for culturally sensitive and competent services that take into account provider and patient characteristics (Alegria, Takeuchi, Canino et al, 2004; Comas-Diaz & Griffith, 1988; Jenkins, 1985; Padilla & Salgado De Snyder, 1985; Ruiz, 2002; Snowden, 2003; Woodward, Dwinell, & Arons, 1992). For example, Oquendo et al (2004) (Oquendo, Lizardi, Greenwald et al, 2004) and others have found that rates of lifetime suicide attempt and major depression vary according to subgroups of Latinos (Kessler, Borges, & Walters, 1999; Ungemack & Guarnaccia, 1998), emphasizing the need to consider individual cultural patient characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This may exist partly because the category of Latino/as consist of culturally heterogeneous groups which differ from one another in many aspects, including their history of migration, their geographical concentration in the US, and other demographic characteristics including family income and educational level (Ungemack and Guarnaccia 1998). While Shaffer (1988;Shaffer et al 1988) found that Latino/a adolescents had relatively low suicide rates compared to whites, attempt rates for Latino/a adolescents in the 9-12th grades in a national sample were higher than their white counterparts from 1991 to (CDC 2006Eaton et al 2006).…”
Section: Race and Ethnicitymentioning
confidence: 98%